Review of the monograph «Osteotomies in the knee joint» V. Orlyanskiy, M. Golovaha - Khmyzov, Sergiy; Baburkina, Olena (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
The authors give their assessment and briefly reveal the content of the monograph by V. Orlyansky and M. Golovakha "Osteotomy in the knee joint"